Persediaan sebelum kehamilan di kalangan etnik India di Semenyih Selangor - Rosnah S,; Wan Aishah WN, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
Pre-pregnancy care is an important strategy in prevention of adverse maternal and fetal health as well as continuity of good child care. In multi-ethnicity country such as Malaysia there are many cultural, religion and beliefs related to certain life stages. Methodology : A cross sectional study was conducted among the Indian ethnic group to assess the prevalence and factors associated with pre-pregnancy care. A study was conducted in Taman Manickavasangam Hulu Langat Selangor among the age group of 18-45 year old women. Result : There were 90 respondents participated in self administered questionnaires. There were 65 respondents (72.2%) married, 24 (26.7%) single and one widow (1.1%). Using a scoring method of analysis (high and low) showed that 55 (61.1%) have high score in knowledge on pre-pregnancy care. The prevalence of pre-pregnancy care practice showed that 63 (70%) scored as high practice. Using correlation analysis showed that there was a significant association between the practice score and increasing age (P=0.03). However, only history of previous pregnancy showed a significant association with the pre-pregnancy care practice and no association found between the practice and knowledge score. Conclusion : Prepregnancy care helps in screening risk factors of women before conception. This will help in prevention of adverse effect on maternal and foetal. Giving awareness on the importance of having prepregnancy care screening may help women to continue practicing good antenatal care.